Screening for modulators of neural network activity in 3D human iPSC-derived cortical spheroids - Woodruff, Grace (PLoS One, 2020)
Human induced Pluripotent Stem Cells (iPSCs) are a powerful tool to dissect the biology of complex human cell types such as those of the central nervous system (CNS). However, robust, high-throughput platforms for reliably measuring activity in human iPSC-derived neuronal cultures are lacking. Here, we assessed 3D cultures of cortical neurons and astrocytes displaying spontaneous, rhythmic, and highly synchronized neural activity that can be visualized as calcium oscillations on standard high-throughput fluorescent readers as a platform for CNS-based discovery efforts. Spontaneous activity and spheroid structure were highly consistent from well-to-well, reference compounds such as TTX, 4-AP, AP5, and NBQX, had expected effects on neural spontaneous activity, demonstrating the presence of functionally integrated neuronal circuitry. Neurospheroid biology was challenged by screening the LOPAC(®1280) library, a collection of 1280 pharmacologically active small molecules. The primary screen identified 111 compounds (8.7%) that modulated neural network activity across a wide range of neural and cellular processes and 16 of 17 compounds chosen for follow-up confirmed the primary screen results. Together, these data demonstrate the suitability and utility of human iPSC-derived neurospheroids as a screening platform for CNS-based drug discovery.